Method for preparing FeCoNiCuCr high-entropy alloy based on MOFs pyrolysis and application of FeCoNiCuCr high-entropy alloy in H2 electrochemical oxidation
The preparation of FeCoNiCuCr high-entropy alloy by MOFs pyrolysis solves the problem of low efficiency of traditional catalysts under alkaline conditions, and improves HOR catalytic activity and reduces costs, providing a new low-cost synthesis method.
Patent Information
- Application Number
- CN202411796640.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-25
AI Technical Summary
The existing H2 electrochemical oxidation catalysts are inefficient under alkaline conditions, and the composition range and formation conditions of the traditional two-/three-way catalysts are restricted by thermodynamic conditions, and the activity modulation range is limited.
FeCoNiCuCr high-entropy alloy is prepared based on MOFs pyrolysis, and the strong electron synergy effect and lattice distortion effect of multi-components are used to promote electrochemical oxidation of H2 under alkaline conditions.
The improvement of HOR catalytic activity, reduced cost, and higher stability than commercial Pt/C catalysts, and a new low-cost synthesis method is provided.
Smart Images

Figure CN119685676A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrocatalysts, and in particular to a method for preparing a FeCoNiCuCr high entropy alloy based on MOFs pyrolysis and an application thereof in H2 electrochemical oxidation. Background Art
[0002] The current world energy is dominated by fossil energy. Fossil energy is non-renewable and highly polluting, which breaks the balance between energy and environment. Moreover, its reserves are not unlimited. This requires humans to develop a new generation of clean energy to alleviate the current contradictions. Hydrogen energy, as an ideal clean energy, is expected to replace traditional fossil fuels and greatly reduce carbon dioxide emissions. Applying hydrogen energy to fuel cells to generate electricity is an efficient hydrogen energy application technology. According to the different electrolytes, hydrogen fuel cells are mainly divided into acidic proton exchange membrane fuel cells (PEMFC) and alkaline anion exchange membrane fuel cells (AEMFC). PEMFC is limited by the slow cathode oxygen reduction reaction (ORR) and the high corrosiveness of acidic media to precious metal catalysts, making PEMFC expensive. The electrolyte environment of AEMFC is milder and less corrosive. The anion exchange membrane can effectively avoid the carbonation of alkaline electrolytes, and the cathode ORR efficiency is significantly improved under alkaline conditions. High-performance non-precious metal ORR catalysts have also been developed. However, in comparison, even the most active platinum-based catalyst on the AEMFC anode has a catalytic efficiency of H2 electrochemical oxidation (HOR) in alkaline media that is 2 to 3 orders of magnitude slower than in acidic media. Therefore, the development of high-performance non-precious metal HOR catalysts is a top priority for AEMFC research. In this regard, Ni-based catalysts have shown excellent activity and corrosion resistance under alkaline conditions, becoming the current mainstream non-precious metal HOR electrocatalyst. At present, the existing Ni-based non-precious metal HOR catalysts are mainly traditional binary or ternary catalysts, and their activity and stability are still far from the requirements of commercial applications. The key to the problem is that the composition range and formation conditions of traditional binary / ternary catalysts are restricted by thermodynamic conditions, and their activity modulation range is limited.
[0003] In response to the above bottlenecks, high entropy alloys composed of five or more metal elements with a content of 5% to 35% of each element have become a promising new type of electrocatalyst due to their unique single-phase solid solution structure. They are not only highly stable, but also have a wide range of composition modulation, which greatly expands the optimization design space of catalysts. The high entropy effect, lattice distortion effect, slow diffusion effect and cocktail effect of high entropy alloys can increase their configuration entropy, uneven atomic arrangement, change electron density, and stimulate potential strong electronic synergy effects, which are helpful to optimize adsorption energy and conductivity, and have rich catalytic active sites and unique electrocatalytic performance. However, as a new type of electrocatalytic material, the research and application of high entropy alloys are still in the early stages, especially the research cases on the use of high entropy alloys in alkaline HOR are very scarce.
[0004] In previous studies, the preparation methods of high-entropy alloys can be mainly divided into four categories: mechanical grinding, sputtering deposition, chemical vapor deposition and atomic layer deposition. The method of preparing alloys by pyrolysis of metal organic frameworks (MOFs) is mainly used in traditional binary or ternary alloys, and high-entropy alloys with more components have not been explored. Therefore, it is of great significance to prepare Ni-based non-precious metal high-entropy alloys by pyrolysis of multi-metal MOFs for application in HOR. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and provide a method for preparing FeCoNiCuCr high entropy alloy based on MOFs pyrolysis and its application in H2 electrochemical oxidation, wherein the catalyst promotes the electrochemical oxidation of H2 under alkaline conditions through the strong electronic synergy and lattice distortion effect of multiple components, so as to solve the technical problems of high cost and low activity of existing HOR catalysts.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] A method for preparing FeCoNiCuCr high entropy alloy based on MOFs pyrolysis comprises the following steps:
[0008] (1) dispersing nitrate in a mixed solution of N,N-dimethylformamide, ethanol and deionized water, ultrasonicating for 30 min at a temperature range of 20 to 25° C., and then transferring to a magnetic stirrer for stirring at a controlled speed of 400 to 600 rpm;
[0009] (2) adding a certain amount of reducing agent to the mixed solution, continuing to stir for 10 to 15 minutes, then adding a certain amount of organic ligand, continuing to stir for 10 minutes, adding a certain amount of surfactant and carbon carrier, and continuing to stir for 4 to 6 hours;
[0010] (3) The mixed solution was transferred to a reaction kettle lined with polytetrafluoroethylene and heated in a constant temperature forced air drying oven at 100°C for 500 min;
[0011] (4) After the reaction kettle is cooled to room temperature, the product is centrifuged and cleaned, and then placed in a vacuum drying oven to dry to obtain a five-component MOFs sample;
[0012] (5) The five-element MOFs sample was ground and transferred to a tube furnace for high-temperature pyrolysis under a reducing atmosphere. When the temperature was cooled to room temperature, a FeCoNiCuCr high-entropy alloy supported on a carbon carrier was obtained.
[0013] Preferably, the nitrate in step (1) is nickel nitrate hexahydrate, cobalt nitrate hexahydrate, chromium nitrate nonahydrate, copper nitrate trihydrate and iron nitrate nonahydrate in a molar mass ratio of (4-5): (4-5): (3-4): (2-3): (2-3), the total concentration of the nitrate is 30.0-40.0 mmol / L, and the volume ratio of N,N-dimethylformamide, ethanol and deionized water is 15:1:1.
[0014] Preferably, the reducing agent in step (2) is sodium borohydride, the organic ligand is 2,5-dihydroxyterephthalic acid, the surfactant is polyvinyl pyrrolidone, the carbon carrier is X-72 carbon, and the mass ratio of the reducing agent, the organic ligand, the surfactant and the carbon carrier is 15:15:50:2.
[0015] Preferably, the centrifugal speed in step (4) is 8000-10000 rpm, the cleaning solution is a mixture of deionized water and ethanol in a volume ratio of 1:(2-3), the temperature of the vacuum drying oven is 60-80°C, and the time is 8-10 hours.
[0016] Preferably, the reducing atmosphere in step (5) is Ar and H2 in a volume ratio of 90:10, the heating rate is 4-6°C / min, the reduction temperature is 700-900°C, and the reduction time is 1-3h.
[0017] The present invention also relates to a FeCoNiCuCr high entropy alloy prepared by the preparation method.
[0018] The present invention also relates to the application of the FeCoNiCuCr high entropy alloy prepared by the above preparation method in H2 electrochemical oxidation in an alkaline electrolyte.
[0019] Compared with the prior art, the present invention has the following advantages:
[0020] (1) The FeCoNiCuCr high entropy alloy prepared in the present invention promotes the mutual synergy between multiple components by introducing the lattice distortion effect in the alloy, effectively regulates the electronic structure of each element of the catalyst, and thus achieves the improvement of the HOR catalytic activity.
[0021] (2) The FeCoNiCuCr high entropy alloy nanocatalyst prepared in the present invention innovatively combines five non-precious metal elements for the first time through MOFs reduction pyrolysis, which greatly reduces the catalyst cost, improves the HOR catalytic activity of the non-precious metal catalyst, and has higher stability than the commercial Pt / C catalyst.
[0022] (3) The synthesis process provided by the present invention is simple, low-cost, and has little pollution, providing a new synthesis method for the low-cost commercial production of high-entropy alloy catalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Fe obtained in Example 1 13 Co 28 Ni 28 Cu 14 Cr 17 X-ray diffraction (XRD) patterns of high entropy alloys.
[0024] Figure 2 Fe obtained in Example 1 13 Co 28 Ni 28 Cu 14 Cr 17 Scanning electron microscope (SEM) image of high entropy alloy.
[0025] Figure 3 (a) (b) are Fe obtained in Example 1 13 Co 28 Ni 28 Cu 14 Cr 17 Energy dispersive X-ray spectroscopy (EDS) image of a high entropy alloy.
[0026] Figure 4 (a) (b) are Fe obtained in Example 1 13 Co 28 Ni 28 Cu 14 Cr 17 Alkaline HOR polarization curves of high entropy alloys and commercial Pt / C.
[0027] Figure 5 Fe obtained in Example 1 13 Co 28 Ni 28 Cu 14 Cr 17 Experimental comparison of the CO resistance performance of high entropy alloys and commercial Pt / C. DETAILED DESCRIPTION
[0028] The present invention is described in detail below in conjunction with the embodiments and drawings. It should be understood that the following contents are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0029] The raw materials required for the present invention can be purchased through commercial channels.
[0030] Example 1
[0031] (1) 45 ml of N,N-dimethylformamide, 3 ml of ethanol and 3 ml of deionized water were weighed to form a mixed solution, 145.4 mg of nickel nitrate hexahydrate, 145.5 mg of cobalt nitrate hexahydrate, 133.5 mg of chromium nitrate nonahydrate, 72.8 mg of copper nitrate trihydrate and 95 mg of ferric nitrate nonahydrate were weighed and dissolved in the mixed solution, and ultrasonicated at 25°C for 30 min, then transferred to a magnetic stirrer for stirring, and the speed was controlled to be 500 rpm.
[0032] (2) Weigh 0.3 g of sodium borohydride and add it to the mixed solution of step (1), continue stirring for 10 min, then add 0.3 g of 2,5-dihydroxyterephthalic acid, continue stirring for 10 min, then add 1 g of polyvinyl pyrrolidone and 40 mg of X-72 carbon, and continue stirring for 5 h.
[0033] (3) The mixed solution was transferred to a reactor lined with polytetrafluoroethylene and heated in a constant temperature forced air drying oven at 100°C for 500 min.
[0034] (4) After the reactor was cooled to room temperature, the product was collected by centrifugation at 8000 rpm, washed three times with a mixed solution of 10 ml of deionized water and 20 ml of ethanol, and then dried in a vacuum drying oven at 60° C. for 10 h.
[0035] (5) The dried sample was ground into powder and transferred to a tube furnace. It was heated to 800 °C and kept at this temperature for 2 h in an Ar / H2 mixed gas with a H2 content of 10% at a heating rate of 5 °C / min to obtain Fe supported on X-72 carbon. 13 Co 28 Ni 28 Cu 14 Cr 17 High entropy alloy.
[0036] Example 2
[0037] (1) 30 ml of N,N-dimethylformamide, 2 ml of ethanol and 2 ml of deionized water were weighed to form a mixed solution, 111.8 mg of nickel nitrate hexahydrate, 91.3 mg of cobalt nitrate hexahydrate, 89.4 mg of chromium nitrate nonahydrate, 58.6 mg of copper nitrate trihydrate and 62.3 mg of ferric nitrate nonahydrate were weighed and dissolved in the mixed solution, and ultrasonicated at 20°C for 30 min, then transferred to a magnetic stirrer for stirring, and the speed was controlled to be 400 rpm.
[0038] (2) Weigh 0.18 g of sodium borohydride and add it to the mixed solution of step (1), continue stirring for 10 min, then add 0.18 g of 2,5-dihydroxyterephthalic acid, continue stirring for 10 min, then add 0.6 g of polyvinyl pyrrolidone and 24 mg of X-72 carbon, and continue stirring for 4 h.
[0039] (3) The mixed solution was transferred to a reactor lined with polytetrafluoroethylene and heated in a constant temperature forced air drying oven at 100°C for 500 min.
[0040] (4) After the reactor was cooled to room temperature, the product was collected by centrifugation at 9000 rpm, washed three times with a mixed solution of 10 ml of deionized water and 25 ml of ethanol, and then dried in a vacuum drying oven at 70° C. for 8 h.
[0041] (5) The dried sample was ground into powder and transferred into a tube furnace, heated to 700°C in an Ar / H2 mixed gas with a H2 content of 10% and kept warm for 1 h at a heating rate of 4°C / min to obtain a FeCoNiCuCr high entropy alloy supported on X-72 carbon.
[0042] Example 3
[0043] (1) 60 ml of N,N-dimethylformamide, 4 ml of ethanol and 4 ml of deionized water were weighed to form a mixed solution, and 200 mg of nickel nitrate hexahydrate, 195.7 mg of cobalt nitrate hexahydrate, 165.5 mg of chromium nitrate nonahydrate, 101.3 mg of copper nitrate trihydrate and 135.4 mg of ferric nitrate nonahydrate were weighed and dissolved in the mixed solution. After ultrasonication at 25°C for 30 min, the mixture was transferred to a magnetic stirrer for stirring at a speed of 600 rpm.
[0044] (2) Weigh 0.45 g of sodium borohydride and add it to the mixed solution of step (1), continue stirring for 10 min, then add 0.45 g of 2,5-dihydroxyterephthalic acid, continue stirring for 10 min, then add 1.5 g of polyvinyl pyrrolidone and 60 mg of X-72 carbon, and continue stirring for 6 h.
[0045] (3) The mixed solution was transferred to a reactor lined with polytetrafluoroethylene and heated in a constant temperature forced air drying oven at 100°C for 500 min.
[0046] (4) After the reactor was cooled to room temperature, the product was collected by centrifugation at 10,000 rpm, washed three times with a mixed solution of 10 ml of deionized water and 30 ml of ethanol, and then dried in a vacuum drying oven at 80° C. for 9 h.
[0047] (5) The dried sample was ground into powder and transferred into a tube furnace, where it was heated to 900°C in an Ar / H2 mixed gas with a H2 content of 10% and kept warm for 3 h at a heating rate of 6°C / min to obtain a FeCoNiCuCr high entropy alloy supported on X-72 carbon.
[0048] The above application method is as follows: 3-5 mg of FeCoNiCuCr high entropy alloy loaded on X-72 carbon is added to 450-600 μl of a mixed solution of isopropanol and Nafion in a volume ratio of (960-980): (20-40), and catalytic ink is obtained by ultrasound. 4-6 μL of the catalytic ink is coated on a glassy carbon electrode, and after drying, a FeCoNiCuCr high entropy alloy working electrode material is obtained. A platinum wire electrode is used as a counter electrode, a saturated calomel electrode is used as a reference electrode, and a 0.1 mol / L KOH solution is used as an electrolyte to form a three-electrode system. H2 is introduced to saturation at room temperature and pressure to perform a HOR performance test.
[0049] Electrochemical performance test
[0050] The alkaline HOR performance test was carried out using the working electrode obtained above. The test used a typical three-electrode system to evaluate the catalytic performance. The system was controlled in real time by a potentiostat. A platinum wire electrode was used as the counter electrode, and a saturated calomel electrode was used as the reference electrode. The test was carried out at room temperature and pressure. A KOH solution with a concentration of 0.1 mol / L was prepared using KOH and deionized water as the electrolyte. Hydrogen was introduced into the electrolyte at a constant flow rate until the electrolyte was saturated with hydrogen, and the flow rate was kept constant throughout the test to ensure that the hydrogen concentration in the electrolyte was always in a saturated state. Before the test, cyclic voltammetry was used to scan 10 circles in a suitable interval at a scan rate of 50 mV / s, and then HOR data was collected. The linear sweep voltammetry test method (LSV) was used to test at a certain scan rate in a constant interval to obtain the HOR reaction activity curve, and the scan rate was 10 mV / s. The test results are as follows Figure 4 and 5 And as shown in Table 1.
[0051] Table 1 Electrochemical performance test results
[0052]
[0053] It can be seen from Table 1 that the FeCoNiCuCr high entropy alloys obtained in Examples 1, 2, and 3 exhibit excellent HOR catalytic activity and stability in 0.1 mol / L KOH solution.
[0054] Figure 4 Fe obtained in Example 1 13 Co 28 Ni 28 Cu 14 Cr 17 The alkaline HOR polarization curves of high entropy alloy and commercial Pt / C show that the Fe 13 Co 28 Ni 28 Cu 14 Cr 17 It has excellent HOR catalytic activity in 0.1 mol / L KOH.
[0055] Figure 5 Fe obtained in Example 1 13 Co 28 Ni 28 Cu 14 Cr 17 The experimental diagram of the resistance of high entropy alloy and commercial Pt / C to CO poisoning shows that the Fe 13 Co 28 Ni 28 Cu 14 Cr 17 It exhibits much better resistance to CO poisoning than commercial Pt / C in 0.1 mol / L KOH.
[0056] The above-listed embodiments are all capable of implementing the present invention for those skilled in the art. However, any modification, replacement, or embellishment of the present invention without departing from the principle of the present invention shall be deemed to be within the protection scope of the present invention.
Claims
1. A method for preparing FeCoNiCuCr high entropy alloy based on MOF pyrolysis, characterized in that: The specific steps include: (1) dispersing nitrate in a mixed solution of N,N-dimethylformamide, ethanol and deionized water, ultrasonicating for 30 min at a temperature range of 20 to 25° C., and then transferring to a magnetic stirrer for stirring at a controlled speed of 400 to 600 rpm; (2) adding a certain amount of reducing agent to the mixed solution, continuing to stir for 10 to 15 minutes, then adding a certain amount of organic ligand, continuing to stir for 10 minutes, adding a certain amount of surfactant and carbon carrier, and continuing to stir for 4 to 6 hours; (3) The mixed solution was transferred into a reaction kettle lined with polytetrafluoroethylene and heated in a constant temperature forced air drying oven at 100° C. for 500 min; (4) After the reaction kettle is cooled to room temperature, the product is centrifuged and cleaned, and then placed in a vacuum drying oven to dry to obtain a five-component MOFs sample; (5) The five-element MOFs sample was ground and transferred to a tube furnace for reduction under a reducing atmosphere. When the temperature was cooled to room temperature, a FeCoNiCuCr high-entropy alloy supported on a carbon carrier was obtained.
2. The preparation method according to claim 1, characterized in that: The molar mass ratio of the nitrate in step (1) is (4-5): (4-5): (3-4): (2-3): (2-3) nickel nitrate hexahydrate, cobalt nitrate hexahydrate, chromium nitrate nonahydrate, copper nitrate trihydrate and iron nitrate nonahydrate, the total concentration of nitrate is 30.0-40.0 mmol / L, and the volume ratio of N,N-dimethylformamide, ethanol and deionized water is 15:1:
1.
3. The method according to claim 1, characterized in that The reducing agent in step (2) is sodium borohydride, the organic ligand is 2,5-dihydroxyterephthalic acid, the surfactant is polyvinyl pyrrolidone, and the carbon carrier is X-72 carbon. The mass ratio of the reducing agent, the organic ligand, the surfactant and the carbon carrier is 15:15:50:
2.
4. The method according to claim 1, characterized in that: The centrifugal speed in step (4) is 8000-10000 rpm, the cleaning solution is a mixture of deionized water and ethanol in a volume ratio of 1:(2-3), the temperature of the vacuum drying oven is 60-80°C, and the time is 8-10 hours.
5. The method according to claim 1, characterized in that The reducing atmosphere in step (5) is Ar and H2 in a volume ratio of 90:10, the heating rate is 4-6°C / min, the reducing temperature is 700-900°C, and the reducing time is 1-3h.
6. A FeCoNiCuCr high entropy alloy prepared by the preparation method according to any one of claims 1 to 5.
7. An application of a FeCoNiCuCr high entropy alloy prepared by the preparation method according to any one of claims 1 to 5 for electrochemical oxidation of H2 in an alkaline electrolyte.